2016
DOI: 10.1186/s40738-016-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective use of percutaneous testis biopsy to optimize IVF-ICSI outcomes: a case series

Abstract: BackgroundSperm quality may degrade during transit through the male reproductive tract in some individuals. In this setting surgically retrieved testicular sperm may outperform ejaculated samples for use with in vitro fertilization (IVF) and intracytoplasmic sperm injection (IVF-ICSI). We sought to describe one center’s experience with the use of fresh testicular sperm after prior failed IVF-ICSI with ejaculated samples.ResultsA retrospective review was conducted evaluating IVF-ICSI cycles performed at a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Our embryo developmental rate is comparable to the results achieved previously in these domestic species. Several human pathologies cause a requirement for the exclusive use of epidydimal spermatozoa [ 31 ]. This work can give a likely opportunity to expand the application of the lyophilization field in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…Our embryo developmental rate is comparable to the results achieved previously in these domestic species. Several human pathologies cause a requirement for the exclusive use of epidydimal spermatozoa [ 31 ]. This work can give a likely opportunity to expand the application of the lyophilization field in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…reactive oxygen species). Also, some preliminary researches have shown the sperm may damage when passing through the male reproductive tract by decreasing the quality of sperms in terms of DNA integrity (6, 20, 21). We demonstrated that the surgically extracted sperm will do better than ejaculated sperm in ICSI and improve pregnancy outcomes in men with idiopathic cryptozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular or epididymal sperm retrieval procedures are available options when the outcome of fertilization by ejaculated sperms is not favorable or when no clinical pregnancy is achieved after multiple attempts with ejaculated fresh sperm cells (6). When both sources of spermatozoa are available (i.e.…”
Section: Introductionmentioning
confidence: 99%